2019
DOI: 10.1111/aji.13170
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, inflammatory settings, and microRNA regulation in the recurrent implantation failure patients with metabolic syndrome

Abstract: ProblemIncreased oxidative stress (OS) and inflammatory factors in metabolic syndrome (MS) patients are considered as risk factors for recurrent implantation failure (RIF). The aim of this study was to investigate OS markers, inflammatory factors, related microRNAs (miRNA) expression, and cytokine and transcription factors RNA expression.Method of studyWe evaluated the frequency of helper T (Th) 17 and regulatory T (Treg) cells in recurrent implantation failure (RIF) women with or without MS. miRNA expression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 63 publications
3
22
0
Order By: Relevance
“…In contrast, the MPO activity was higher in MetS subjects compared to those without MetS. Similar results were previously observed, showing that recurrent implantation failure patients with MetS (RIF-MS) decreased SOD and CAT levels in comparison with a control group, whereas the MPO levels increased in the MetS group [16]. Moreover, it has been also reported that MPO activity progressively increases with obesity and MetS [44].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, the MPO activity was higher in MetS subjects compared to those without MetS. Similar results were previously observed, showing that recurrent implantation failure patients with MetS (RIF-MS) decreased SOD and CAT levels in comparison with a control group, whereas the MPO levels increased in the MetS group [16]. Moreover, it has been also reported that MPO activity progressively increases with obesity and MetS [44].…”
Section: Discussionsupporting
confidence: 87%
“…This study reveals that inflammatory mediators in plasma, IL-6, and TNFα, exhibited higher significant levels in patients with MetS in comparison to patients without MetS. TNFα circulates throughout the body responding to stimuli, such as infectious agents or tissue injury, altering properties of vascular endothelial cells, and regulating metabolic activities of other tissues [16,46]. The expression of IL-6 is readily induced by a variety of cytokines, lipopolysaccharide, or viral infections; for these reasons, high IL-6 levels are associated with inflammatory responses [54].…”
Section: Discussionmentioning
confidence: 78%
“…Sheikhansari et al have shown increased OxS and inflammatory factors in MetS women as compared to healthy probands. Moreover, MetS elicited decreased expression of miR-223 and miR-146a and upregulation of miR-21 in peripheral blood mononuclear cells (PBMCs) [286]. Other studies indicated that downregulation of miR-223 promotes increase of IL-1β and IL-6 production [287].…”
Section: Microrna In Mets-a Link With Chronic Inflammation Related Tomentioning
confidence: 99%
“…GSH was found to be decreased only in Pakistani exposed group. A decrease in activity of these enzymes would favor the accumulation of free oxygen radicals in erythrocytes and other cells, leading to tissue damage which could be significantly detrimental when pesticides exposure persists over several years and may ultimately be responsible for multipletissue and organ damages (neurological, metabolic, hepatic, and renal) [45][46][47]. We also observed an increase in MDA and FRAP in OP-exposed individuals.…”
Section: Discussionmentioning
confidence: 63%